STUDI KOMPARATIF PENENTUAN TARIF JASA RAWAT INAP RUMAH SAKIT DENGAN METODE ACTIVITY-BASED COSTING PADA RUMAH SAKIT SITI KHODIJAH SIDOARJO - RAISAH FAKHIRA, AMINAH (Jurnal Akuntansi AKUNESA, 2017)
This present study aimed to calculating the inpatient room rate employed by Siti Khodijah Hospital, calculating the inpatient room rate at Siti Khodijah Hospital by Activity-Based Costing method, and to know the difference between inpatient room rate at Siti Khodijah hospital which using method Activity-Based Costing system. This research was conducted at Siti Khodijah Hospital which is located at Street Pahlawan, Sepanjang, Sidoarjo. The method of analysis used is descriptive qualitative with case study design that is analysis of the calculation tariffs used by hospital now, calculate the tariff by cost method based on Activity-Based Costing, then compare tariffs based on traditional methods and Activity-Based Costing. The results of this study indicate that result of research by using Activity-Based Costing method shows that for the VVIP class, VIP A, VIP B provide smaller results (undercosting) while for class I, II A, II B, II C and class III provide greater results (overcosting) because of hospital tariff determination using cross subsidy method which aims to balance service for the economically weak community so that hospitals can cover the shortage of costs. Keywords: Tarif, Inpatient, Activity-Based Costing System